2008
DOI: 10.1148/radiol.2461062075
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Normal-appearing White Matter Damage in Neuromyelitis Optica: Diffusion-Tensor MR Imaging

Abstract: http://radiology.rsnajnls.org/cgi/content/full/2461062075/DC1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
67
4
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 25 publications
10
67
4
3
Order By: Relevance
“…40,41 Similarly, decreased FA and AD and increased RD have been demonstrated in patients with neuromyelitis optica. 42,43 These changes involve multiple, major WM tracts in the normal-appearing WM, accumulate with increasing disease duration, and are probably related to both demyelination and Wallerian degeneration. 42,43 A global decrease in WM integrity throughout the brain was observed in multiple major fiber tracts that control a wide range of brain functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40,41 Similarly, decreased FA and AD and increased RD have been demonstrated in patients with neuromyelitis optica. 42,43 These changes involve multiple, major WM tracts in the normal-appearing WM, accumulate with increasing disease duration, and are probably related to both demyelination and Wallerian degeneration. 42,43 A global decrease in WM integrity throughout the brain was observed in multiple major fiber tracts that control a wide range of brain functions.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 These changes involve multiple, major WM tracts in the normal-appearing WM, accumulate with increasing disease duration, and are probably related to both demyelination and Wallerian degeneration. 42,43 A global decrease in WM integrity throughout the brain was observed in multiple major fiber tracts that control a wide range of brain functions. The CNS manifestations in pSS are heterogeneous, manifested as focal or diffuse involvement.…”
Section: Discussionmentioning
confidence: 99%
“…These methods have shown that ADEM, NMO and Leber optic neuropathy are associ ated with less diffuse tissue damage than is typical of MS, and this factor could be used as a distinguishing feature. [35][36][37][38] However, prospective studies are required to systematically assess the advantages of advanced techniques over conventional MRI in the diagnosis and prognosis of MS, and in the facilitation of prompt treatment decisions.…”
Section: -34mentioning
confidence: 99%
“…Such areas are better evaluated with advanced MR imaging techniques, such as diffusion tensor MR imaging (DTI). This technique allows the assessment of tissues at a cellular level, once the microstructural architecture preservation of the white matter tracts are evaluated by water molecular diffusion along the axon fibers 6,7 . The DTI consists of three eigenvectors and to each one there is a corresponding diffusion axis that reports to the direction of diffusive water motion.…”
Section: Diffusion Tensor Magnetic Resonance Imaging May Show Abnormamentioning
confidence: 99%